Load Frequency Control Using Augmentation PI-LQR Controller For A Two-Area Hydropower System - Mohd Shaharudin, Nabilah (2019)
Hydropower is a vital renewable energy source which harnesses the power of moving water to produce electricity. Maintaining synchronism between different parts of hydropower is getting difficult over time. Frequency deviation can cause stalling in loads. If synchronism between generator and the power systems is lost at any time, voltage and current fluctuations may have happened that give catastrophic effect to the end users and power systems. A large frequency deviation can harm the equipment, delay load performance, cause the transmission line to be overloaded, damage protection schemes and ultimately lead to frequency instability. In case of interconnected power system, any small sudden load change in any of the areas causes the fluctuation of the frequencies of each and every areas and also there is fluctuation in the tie line. Many conventional load frequency control (LFC) with conventional Proportional-Integral (PI) have successfully stabilized the system. However, the speed of the recovery time is highly depending on the integral and proportional gain of PI controller. Increasing the gain may cause instability as the closed loop system tends to move system poles to unstable region. Therefore, this research proposes the augmentation of Linear Quadratic Regulator (LQR) with conventional PI in order to obtain a fast settling time without the need to judiciously adjust the PI parameters. The main goals of LFC are, to maintain the real frequency system to its acceptable limit i.e. ± 2.5 Hz while maintaining the power exchange among the control areas at specific value. To formulate the control scheme, the dynamic of the hydropower system is modeled in the time domain. The hydropower unit consists of the hydro governor, transient droop compensation, hydro turbine and load. Afterward, the LFC is designed via conventional PI controller wih Ziegler Nichols tuning. The LQR is then augmented to the conventional PI. In this stage, the dynamic of PI controller is embedded into the 11 × 11 state variable model of the hydropower system. The LQR parameters are obtained based on the algebraic Riccati equation where the stability is guaranteed by Lyapunov stability criteria. The effectiveness and the efficacy of the proposed PI-LQR and the conventional PI in LFC is validated via simulation in MATLAB with SIMULINK® toolbox. The comparative results showed that the closed loop two-area hydropower system with PI-LQR able to achieve asymptotic stability despite the injection of multifarious load perturbations. Compared to LFC with conventional PI controller, the settling time of LFC with PI-LQR has reduced at almost 85% for both area 1 and area 2. Whereas, 93.56% reduction in settling time for the tie line power changes is recorded. Moreover, LFC with PI-LQR managed to reduce the settling time for the system frequency at almost 95.26% when the perturbation occurs. In conclusion, the result shows that the LFC with PI-LQR controller guarantee faster transient with lower integral of absolute error as compared with the conventional PI controller.